Kajian Literatur Evolusi Kuda: Perubahan Kaki Dan Perubahan Gigi Kuda Berdasarkan Penemuan Fosil - Nafasya Rahmandini; Nashwa Intana Putri; Virna Fianarita Rahmawati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Evolution is characterized by changes over time with one or more inherited traits that we often find in populations of organisms. Fossils themselves can be said to be traces/remains/marks of a life of an organism (animal/plant) that can be directly or indirectly preserved with the earth's crust, naturally occurring and usually solid/hard with a geological age of more than 11,000 years. Horse evolution is one of the interesting adaptations, with morphological changes related to environmental changes. The purpose of this study was to determine the evolution of horses from the fossils found and, to find out how to adapt and the changes that occur from the environment and factors of natural selection. The method used in this study is a literature review from several reference sources. Horse evolution shows how species can adapt to the environment through significant morphological changes, such as a reduction in the number of fingers and an increase in body size. and the role of natural selection in forming physical characteristics that support survival.